2021
DOI: 10.1039/d1cy00287b
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic decomposition of methane into hydrogen and high-value carbons: combined experimental and DFT computational study

Abstract: Thermocatalytic decomposition (TCD) of methane can produce hydrogen and valuable nanocarbon co-products with low to near-zero CO2 emission. In this study, a series of Pd promoted Ni catalysts, prepared with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…As a result, acid treatment can be used to dissolve metals on the tip or base of the CNT in order to purify grown CNT . In our recent study, a MCP process with cyclic reaction-regeneration was experimentally demonstrated . The results showed that the Ni–Pd/CNT catalyst can be regenerated and re-applied.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…As a result, acid treatment can be used to dissolve metals on the tip or base of the CNT in order to purify grown CNT . In our recent study, a MCP process with cyclic reaction-regeneration was experimentally demonstrated . The results showed that the Ni–Pd/CNT catalyst can be regenerated and re-applied.…”
Section: Introductionmentioning
confidence: 98%
“…As a result, a base-grown catalyst design concept was reported with the objective to retain metal on the surface . Other than supported catalysts, liquid metal and molten salts were used as catalysts for methane conversion into hydrogen. , Mechanistic studies were carried out on the formation of carbon nanomaterials over metal-supported catalysts. Progress has been made on understanding the fundamental reaction pathways over a carbon nanotube (CNT)-supported binary metal catalyst by using density functional theory. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the problem is that the active metal particles are easily encapsulated with carbon, causing a rapid deactivation of the catalyst. Therefore, many studies have been devoted to enhancing the catalyst performance 12‐20 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many studies have been devoted to enhancing the catalyst performance. [12][13][14][15][16][17][18][19][20] It has been indicated that the addition of a second metal to the nickel catalyst can improve the catalytic performance of CDM. 21 In this regard, Cu-promoted Ni catalysts have been widely investigated and demonstrated to enhance the catalytic life and carbon yield in CDM.…”
Section: Introductionmentioning
confidence: 99%